Electrical conductivity measurement of λ DNA molecules by conductive atomic force microscopy. (8th November 2021) - Wang, Ying; Xie, Ying; Gao, Mingyan; Zhang, Wenxiao; Liu, Lanjiao; Qu, Yingmin; Wang, Jiajia; Hu, Cuihua; Song, Zhengxun; Wang, Zuobin
Abstract: Conductive atomic force microscopy (C-AFM) is a powerful tool used in the microelectronics analysis by applying a certain bias voltage between the conducting probe and the sample and obtaining the electrical information of sample. In this work, the surface morphological information and current images of the lambda DNA ( λ DNA) molecules with different distributions were obtained by C-AFM. The 1 and 10 ng μ l −1 DNA solutions were dripped onto mica sheets for making randomly distributed DNA and DNA network samples, and another 1 ng μ l −1 DNA sample was placed in a DC electric field with a voltage of 2 V before being dried for stretching the DNA sample. The results show that the current flowing through DNA networks was significantly higher than the stretched and random distribution of DNA in the experiment. The I – V curve of DNA networks was obtained by changing the bias voltage of C-AFM from −9 to 9 V. The currents flowing through stretched DNA at different pH values were studied. When the pH was 7, the current was the smallest, and the current was gradually increased as the solution became acidic or alkaline.